STEAM Education - Esty Setyo Utaminingsih; Ellianawati Ellianawati; Sri Sumartiningsih; Maria Ayu Puspita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The International Society for Technology in Education (ISTE) requires institutional education to adapt to rapid technology and prepare students to compete internationally by using e-learning media in the classroom. The purpose of the study's literature is to strengthen every argument about STEAM education. Support argument required originating data source from secondary data. The method used in this research is the study literature method. Data collection techniques through collecting articles on STEAM, STEAM education, and technology in the learning process. Databases used for journal searches include Elsevier, Emerald, Springer, Research Gate, Academia Edu, Google Scholar, and Publish or Perish. The validity test of the data through several stages. The process starts with data collection, reduction, presentation, and withdrawal conclusion. The result of this study is that STEAM builds human resources who can think critically, logically, and systematically and have global competitiveness. Implementing STEAM education enables students to understand the importance of integrating multiple disciplines. Moreover, learners can improve their logical thinking and provide comprehensive opportunities for students to practice their thinking skills.